VOZDELYVANIE ZARUBEJNYX SORTOV EJEVIKI RODA (RUBUS NENSENSIS) I (RUBUS FRUTICOSUS) V KLIMATIChESKIH USLOVIYAX ANDIJANA (Academicia Globe: Inderscience Research, 2022)
Large-fruited and productive varieties of the monkey in many cases were created by European breeders, and their introduction and breeding in the hot climate of Uzbekistan requires a special approach. The article describes the breeding experiences of the Bjezina and Chachanska varieties of Maimunjon in various conditions of mixed, stony and saline soils of Uzbekistan. Also, the results of comparing the biological and pharmaceutical properties of some varieties of wild and cultivated species are described.